On micromechanical damage modeling in geomechanics: Influence of numerical integration scheme - Levasseur, S.; Collin, F.; Charlier, R.; Kondo, D. (Journal of computational and applied mathematics, 2013)
Tunnel excavations in deep rocks provide stress perturbations which initiate diffuse and/or localized damage propagation in the material. This damage phenomenon can lead to significant irreversible deformations and changes in rock properties. In this paper, we propose to model such behavior by considering a micromechanically-based damage approach. The resulting micromechanical model, which also accounts for initial stress, is described and assessed through the numerical analysis of a synthetic tunnel drilling in Opalinus Clay. A particular emphasis is put on the numerical integration of the model. In particular, an appropriate choice of the latter is required to ensure the numerical stability and a confident prediction of excavation damaged zone around tunnels.